Co-occurrence of multi-mycotoxins in wheat grains harvested in Anhui province, China. (February 2019) - Xu, Wenjing; Han, Xiaomin; Li, Fengqin
Abstract: The aim was to evaluate the occurrence of Fusarium mycotoxins in 370 wheat grain samples harvested in 2015 from Anhui province of China. Deoxynivalenol (DON), deoxynivalenol-3-glucoside (D-3-G), 3- and 15-acetyl-deoxynivalenol (3-A-DON and 15-A-DON), nivalenol (NIV), fusarenon-X (FX) and zearalenone (ZEN) were analyzed by a high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method. The thousand kernel weight of wheat samples was also conducted. DON is the most frequent and abundant Fusarium mycotoxins detected, then followed by D-3-G, NIV, 3-A-DON, ZEN, 15-A-DON and FX. A total of 368 samples are positive for more than one Fusarium mycotoxins analyzed. Moreover, there are positive correlations between DON concentration and other six Fusarium mycotoxins. While, the thousand kernel weight of wheat has a negative correlation with ZEN concentration. These findings suggest an urgent need to monitor contamination of these toxins and raise concern to the high-consuming population of wheat in China. Highlights: Deoxynivalenol is the most abundant and frequent Fusarium toxins detected in wheat samples. Co-occurrence of Fusarium toxins in wheat samples are widely detected. There are positive correlations between Fusarium toxins. The thousand kernel weight of wheat has a negative correlation with zearalenone concentration.